Examining R.O. Winstedt’s perspective on the impact of Islam and Hinduism on Malay culture: a critical analysis / Mohd Farhan Abd Rahman ... [et al.] - Abd Rahman, Mohd Farhan; Abd Razak, Muhd Imran; Lokman, Md Azzaat Ahsanie; Mustafar, Mohd Zaid; Mohd Nason, Amir (Universiti Teknologi MARA, Perak, 2023)
R.O. Winstedt, a British administrator who served in Malaya, was an orientalist whose thinking was influenced by logical empirical positivism. This philosophy emphasized the use of intellect as the primary approach to acquiring facts through systematic and thorough research methods. Winstedt's perspective rejected the use of revelation or religious proofs as evidence in historical studies, considering them irrelevant. This article examines Winstedt's viewpoint on the impact of Islam and Hinduism on the lives of Malays, focusing on four selected writings and academic perspectives toward his ideas. The authors employed historiography, comparisons, and content analysis to analyse these views. The study revealed that Winstedt's approach to assessing the influence of Hinduism on Malay community life, particularly in areas such as culture, law, and mythology, was questionable and biased. He believed that the community's development and civilization were shaped by Hindu culture, disregarding the contributions of Islam. This understanding stemmed from Eurocentric thinking, which placed Europe at the centre and portrayed it as a superior and civilized nation compared to others. This Eurocentrism led to a lack of understanding regarding the essence of Islam. It propagated the idea that European nations were the "ambassadors of civilization" and the saviours of less civilized peoples.